Biodiversity alleviates the decrease of grassland multifunctionality under grazing disturbance: A global meta‐analysis. Issue 1 (1st October 2021) - Zhang, Ruiyang; Tian, Dashuan; Chen, Han Y. H.; Seabloom, Eric W.; Han, Guodong; Wang, Shaopeng; Yu, Guirui; Li, Zhaolei; Niu, Shuli
Abstract: Aim: Biodiversity drives the delivery of multiple ecosystem functions related to carbon and nutrient cycling (ecosystem multifunctionality, EMF), and biodiversity and ecosystem functioning are strongly threatened by intensive grazing in grasslands. However, it remains unclear how biodiversity regulates EMF changes in response to intensive grazing. Location: Global. Time period: From 1992 to 2018. Major taxa studied: Grassland. Methods: Here, we conducted a global synthesis using 373 paired observations from 90 published studies to address the responses of plant diversity, EMF and their relationships to grazing disturbance depending on grazing intensity, livestock type, grazing duration, and climatic aridity. Results: Our results showed that EMF significantly decreased with increasing grazing intensity, but the negative EMF response was alleviated at high levels of plant diversity. The grazing‐induced changes in EMF increased linearly with the changes in plant diversity, with the slopes increasing by 78.9% from light to heavy grazing. In addition, the grazing‐induced decrease of EMF was stronger with longer grazing duration and more arid climates. Structural equation models suggested that grazing intensity reduced EMF largely via decreasing plant diversity, whereas upsizing livestock type promoted EMF by increasing plant diversity. Main conclusions: This study highlights the key role of biodiversity in mediating EMF in response to intensifying grazing disturbance. We call for conservation of biodiversity to maintain grassland multifunctionality and services.